Table Tennis Technique Mastery Level of STKIP Pasundan Students: Analysis of Internal and External Factors Affecting Basic Technique Performance - Hasmarita, sony; Wirasasmita, Ricky; Saputra, Mochammad Yusril (STKIP Pasundan, 2025)
This study analyzes basic table tennis technique mastery among STKIP Pasundan students and identifies influencing factors. Using quantitative descriptive methods, 60 students from 150 Physical Education students were selected through simple random sampling. Research instruments included observation sheets assessing six basic techniques (grip, stance, footwork, serve, forehand, backhand) and Likert scale questionnaires measuring internal factors (motivation, interest, physical condition) and external factors (facilities, social support, learning methods). Results showed 56.7% of students achieved moderate mastery, 16.6% high, and 26.7% low. Service technique had highest mastery (25%), footwork lowest (40%). Internally, motivation was high (65%) but physical condition adequate for only 40%. Externally, facilities (63.3%) and learning methods (60%) were inadequate, though social support was sufficient (53.3%). Conclusion: Students predominantly achieve moderate technique mastery. Enhanced motivation, physical conditioning, improved facilities, and innovative teaching methods are essential for advancing table tennis technique proficiency.Coba lagiClaude dapat membuat kesalahan. Periksa kembali setiap respons.